The Effect of Fish Thickness on Dryness Level and Time for Drying Fish - Azizah, Nur; Asfiyanti, Nurul Aini; Hasibuan, Melisa; Jannah, Miftahul; Gustari, Rinda; Hasibuan, Riski Sakinah (International Journal of Natural Science and Engineering, 2021)
Drying fish is one way of preserving fish by reducing the water content so that the activity of microorganisms can be reduced. Preservation by drying is intended to extend the shelf life of fish. The method used in this research is using the experimental method. The data used in this study include data regarding the process, what materials will be carried out in this research. In this study, there were several problems in the drying time of fish. The data collection technique was the implementation of experiments and documentation. The conclusion of this research is sunlight, fish thickness, and drying time affect the drying rate of fish. Fish that get enough sunlight and have a small and thin shape will dry faster than fish with thick meat, such as catfish and catfish. Fish dried without salt and get enough sunlight will usually dry faster than fish given salt. Except for fish that have thick and oily meat usually dry longer. The drying time of fish varies depending on the thickness of the fish and the sunlight it gets.